Isotropic octet-truss lattice structure design and anisotropy control strategies for implant application - Feng, Jiawei; Liu, Bo; Lin, Zhiwei; Fu, Jianzhong (Materials & design, 2021)
In the field of bone implantation, there is a large demand for isotropic lattice with appropriate mechanical properties and porosity. Two isotropic lattice structure design and anisotropy control strategies are proposed in this work. The first way to acquire isotropic lattice structures is to combine the cross-frustum with octet-truss structure. Then the anisotropy can be adjusted by changing the frustum parameters. The second strategy is implemented in the space of normal lattice to generate hierarchical structures to achieve lattice anisotropy control by changing the inner and outer diameters. In virtue of homogenization method and finite element analysis (FEA), the relationship between elastic modulus, anisotropy and lattice parameters can be established. Based on that, the lattice structures with required elastic modulus and isotropy can be obtained. In addition, the isotropic lattice structures acquired by these two methods are applied as acetabular cup implant in this work. Compared with normal octet-truss, experimental results validate that the elastic modulus of designed lattice implant fluctuates significantly smaller. The standard deviation of elastic modulus in different directions is reduced by about 80%. [Display omitted] •Isotropic lattice structure design methods were proposed based on frustum and hierarchical lattice.•The relationship between elastic modulus, anisotropy and lattice parameters were established for performance control.•Acetabular cup implants were designed with the proposed isotropic lattice structures.